2018
DOI: 10.1002/jsfa.8907
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Leuconostoc strains isolated from artisanal Serrano Catarinense cheese for use as adjuncts in cheese manufacture

Abstract: These results allowed the selection of five strains (UEL 04, UEL 12, UEL 18, UEL 21 and UEL 28) as good candidates for use as adjunct cultures for cheese manufacture. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…Furthermore, the absence of L. monocytogenes surveillance studies from the raw material could contribute to increasing the risk of contamination with this pathogenic microorganism. Our results would support the potential application of these lactobacilli as new protective cultures to limit the growth of this pathogen during the manufacture of dairy products, such as cheeses, which require similar conditions to the ones tested in this work (Seixas et al, ).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Furthermore, the absence of L. monocytogenes surveillance studies from the raw material could contribute to increasing the risk of contamination with this pathogenic microorganism. Our results would support the potential application of these lactobacilli as new protective cultures to limit the growth of this pathogen during the manufacture of dairy products, such as cheeses, which require similar conditions to the ones tested in this work (Seixas et al, ).…”
Section: Resultssupporting
confidence: 80%
“…In general, while there are numerous starter cultures widely marketed and thus easily available for their use in the dairy sector, protective cultures that effectively reduce pathogenic growth are unfortunately scarce in most Latin American countries (Almeida da Costa et al, ; Pujato et al, ). Therefore, the careful selection and potential application of safe microorganisms for the development of new protective cultures would represent an interesting technological achievement that could contribute to the safety of dairy products (Seixas, Rios, Martinez de Oliveira, Beloti, & Poveda, ). Consequently, this approach would be particularly important in Argentina as well as in many other developing countries because the search of L. monocytogenes in milk as raw material has not been yet regulated (CAA, ).…”
Section: Introductionmentioning
confidence: 99%
“…It exhibits antibacterial effect against bacteria that cause cheese spoilage. Additionally, Leuconostoc has been proven to inhibit pathogen growth and can be used as a safe probiotic for further research [42,43]. Indeed, several strains belonging to Leuconostoc genus are regarded as potential probiotics owing to various health beneficial effects [44].…”
Section: Discussionmentioning
confidence: 99%
“…Le. lactis and S. equorum are available as commercial cultures for cheese making to enhance the flavor and color of surface-ripened cheeses (31)(32)(33). The surface cultures used in this study showed the ability to grow under simulated cheese-ripening conditions and displayed some enzymatic activities involved in proteolysis, catabolism of FAAs, and lipolysis.…”
mentioning
confidence: 93%